Exploratory Spatial Mapping of the Occurrence of Antimicrobial Resistance in E. coli in the Community - Akke Vellinga; Martin Cormican; Andrew W. Murphy; Belinda Hanahoe; Ronan Hennessy; Sandra Galvin; Niall Bergin (MDPI AG, 2013)
The use of antimicrobials over the past six decades has been associated with the emergence and dissemination of antimicrobial-resistant bacteria. To explore local geographical patterns in the occurrence of acquired antimicrobial resistance (AMR), AMR of E. coli causing urinary tract infections (UTI) in the community in the West of Ireland was mapped. All adult patients consulting with a suspected UTI in 22 general practices in the West of Ireland over a nine-month study period were requested to supply a urine sample. Those with a laboratory confirmed E. coli infection were included (n = 752) in the study. Antimicrobial susceptibility testing was performed by standardized disc diffusion. Patient addresses were geocoded. The diameters of the zone of inhibition of growth for trimethoprim (5 μg) and ciprofloxacin (5 μg) for the relevant isolate was mapped against the patient address using ArcGIS software. A series of maps illustrating spatial distribution of AMR in the West of Ireland were generated. The spatial data demonstrated a higher proportion of isolates with AMR from urban areas. Some rural areas also showed high levels of resistant E. coli. Our study is the first to demonstrate the feasibility of using a geographical information system (GIS) platform for routine visual geographical analysis of AMR data in Ireland. Routine presentation of AMR data in this format may be valuable in understanding AMR trends at a local level.